Utilization of Local Natural Resources in The Development of UMKM Products in The Tourist Village of Thousand Flowers Karo District - Wilson, Jerry; Lishanata, Mida; Wahyu Sastra Pradnyana, I Putu (Cattleya Darmaya Fortuna, 2025)
Village of Thousand Flowers Tourism in Karo Regency has significant potential in utilizing local natural resources for the development of Micro, Small, and Medium Enterprises (MSMEs). This research aims to analyze how local natural resources can be optimized in the process of developing MSME products in this area. The research methodology involves surveys, interviews, and observations of MSME actors in the Village of Thousand Flowers Tourism. Qualitative analysis is applied to the collected data to identify the types of local natural resources that can be utilized, as well as strategies that can be implemented in the development of MSME products. The results indicate that the Village of Thousand Flowers Tourism possesses rich local natural resources in the form of flora and fauna that can serve as raw materials for MSME products. Some potential products include handicrafts, culinary items, and souvenirs that reflect the unique culture and local environment. The active involvement of the local community in the production process is crucial for the successful optimization of these natural resources. The application of creative economic principles and local value addition can be a solution to enhance the competitiveness of MSME products from the Village of Thousand Flowers Tourism. Support from local governments, business actors, and the community is essential in creating a conducive environment for the development of MSME products based on local natural resources. This research contributes strategically to the development of MSMEs based on local natural resources in the Village of Thousand Flowers Tourism, Karo Regency. The findings are expected to serve as a reference for stakeholders in fostering sustainable local economic potential